New Architectures for Designed Catalysts: Selective Oxidation using AgAu Nanoparticles on Colloid‐Templated Silica. Issue 8 (30th November 2017) - Shirman, Tanya; Lattimer, Judith; Luneau, Mathilde; Shirman, Elijah; Reece, Christian; Aizenberg, Michael; Madix, Robert J.; Aizenberg, Joanna; Friend, Cynthia M.
Abstract: Invited for the cover of this issue are the groups of Joanna Aizenberg and Cynthia M. Friend from Harvard University, Cambridge, USA. The image depicts a templated silica matrix decorated with AuAg nanoparticles catalyzing the oxidative coupling of methanol to form methyl formate. Read the full text of the article at 10.1002/chem.201704552 . Abstract : "… this research enables the design of a variety of mono‐ and multi‐metallic catalysts for use in various industrially important reactions " Read more about the story behind the cover in the Cover Profile and about the research itself on page 1833 ff. (DOI:10.1002/chem.201704552 ).